Interaction of cation/anion exchange membrane with vanadium electrolyte in redox flow battery - Chan, Kai Ler (2017)
The Vanadium Redox Flow Battery (VRFB) uses a single active element for both half- cells, limiting cross contamination impacts while maintaining benefits of high energy efficiency and large scale implementation via external energy storage. The VRFB consists of vanadium electrolytes in two half-cells which undergo redox reactions to transfer electrons across two electrodes as ions pass through the exchange membrane between the half-cells to balance the charge. VRFB implements vanadium in both half-cells, elimination cross-contamination problems. However, vanadium ion crossover is observed for cation exchange membranes (CEM) such as Nafion, reducing cell capacity over time. Coupled with high membrane costs, this encourages research into the alternative anion exchange membranes (AEM), such as Fumatech membrane. Fumatech AEM bears chemical stability and ion selectivity required for this application, though selectively transferring hydroxyl anions instead of protons. Using UV-Visible Spectroscopy and Energy Dispersive Spectroscopy (EDS), this AEM was found to adsorb significant amounts of vanadium relative to the CEM, particularly V(V), likely contributing to high resistivity and thus poor cell performance. Thermal sensitivity of the AEM is found to be higher, making it unsuitable for high temperature applications. Electrolyte transfer was also observed for the AEM. Vanadium crossover was reconfirmed in Nafion CEM, though the impact on cell performance is still less significant compared to Fumatech AEM. An overall comparison of cell parameters for both membranes shows Nafion CEM providing greater practicality for VRFB application.